Deploying Red Hat HPC Cluster in Al-Neelain University Labs - Mohamed Mahagoub Abbas Mohamed,; Noha Ahmed Ishaq Saleh, (International Journal of Computers and Informatics, 2024)
By using HPC Cluster, users can expedite their HPC workloads on elastic resources as needed and save money by choosing from low-cost pricing models that match utilization needs. The researchers preferred the red hat open-source solution because it is the easiest pre-integrated, pre-tested, and certified configurations. Most HPC software forgets about keys like storage and data integrity also I/O performance, So the researchers recommend using third party tools and monitors to reduce this weakness.
Keywords: HPC Cluster; Red Hat; Al-Neelain University